Chronopharmacology of cardiovascular medications - Lemmer, Björn (Biological rhythm research, 2007)
The cardiovascular system is well organized in time. Mechanisms of regulation and pathophysiological events are not evenly distributed over the 24-h scale. Moreover, certain diseases may even alter the physiological circadian pattern in the cardiovascular system. This observation bares implications for drug treatment, e.g. regarding drug formulations and dosing time intervals. Pitfalls may arise from neglecting circadian phase-dependency in pharmacokinetics and in the concentration-dependent effect relationship. Moreover, different types of drugs may be superior to others when circadian time-related symptoms are concerned. There is sound evidence that “time-of-day” has to be included in our diagnostic and therapeutic strategies.